The characteristics of turn rhythm patterns in the men's hammer throw - Hirose, K.; Ohyama, B. K.; Ogata, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: The hammer throwers use turn movement to accelerate the hammer head. The duration time of turn is showed in previous researches (Gutieérrez et al., 2002; Isele and Nixdorf, 2010). Bartonietz (2000) noted that the turn rhythm is one of the important components for the hammer throw technique. However, turn rhythm patterns were seldom studied in previous researches. The aim of this study is to identify the specific rhythm pattern for each thrower. METHODS: We analyzed the duration time of turn for the 116 men`s hammer throwers in the competitions. Their range of record was 49.11-85.20m and all throwers use 4 turns. These competitions included the Olympic Games, the World Championships, the Asian/European Championships and the Local Championships. We determined the duration time of turn from recorded movies and downloaded publicly available Internet broadcasts. Frame rates of analyzed movies were 30 to 100 fps. The duration time of turn is measured from instant of right foot takeoff from the ground in the first turn to instant of release in the last turn. Ward`s method of the cluster analysis was used to classify turn rhythm patterns. RESULTS: Turn rhythm patterns were divided into 3 types: fast start (F-type, n=29), slow start (S-type, n=38), and middle (M-type, n=50). There were significant correlations between the total time of turn and the throwing record in all types. There were no significant differences in the throwing record between three types. The duration time at 1st turn of F-type was significantly shorter than M-type and S-type. The duration time at 4th turn of F-type was significantly longer than M-type and S-type. Total time of F-type was significantly shorter than M-type and S-type. DISCUSSION: Turn rhythm patterns are not the determinant for throwing record. In addition, decreasing the total time of turn leads to a longer throwing distance for all types. These results suggest that each turn rhythm pattern corresponds to different strategy to accelerate the hammer head and we can not suggest athletes/coaches should select what type of turn rhythm pattern. The duration time at 1st turn of F-type is shorter, but 4th turn is longer. In addition, F-type requires shorter total time to throw the same record compared to other types. In contrast, the duration time at 1st turn of S-type is longer, but 4th turn is shorter. Therefore, S-type requires faster speed than that of F-type at 4th turn.